The contemporary spell of heat stroke in Karachi amid global warming and power crisis: a threatened call for medical emergency - Saadat, Ayesha; Zubair, Rooja; Siddiqui, Urooba Inam; Mughal, Sanila (Frontiers in Public Health, 2025)
The study examines the impact of population density, air pollution, and temperature on heat stroke cases in Karachi, focusing on stroke-related mortality from 2010 to 2024. It develops an intelligent system for adaptive forecasting, incorporating population increase, air quality, meteorological activity, and mortality data, presenting urban vulnerability to health crises. A Pearson correlation analysis was used to determine the association between these factors, which makes it possible to present urban vulnerability to health crises from various angles that are systematically relevant and interdependent at the same time. This study is unique because it takes an integrated approach, relating urban stressors and climate conditions to public health outcomes in Karachi, a context that has been neglected in previous studies.